The Development of a Bilateral System in National Inheritance Law Grounded in Social Justice - Perwitasari, Dita; Santoso, Budi; Yunanto, Yunanto (Pancasila and Law Review, 2024)
The unresolved conflicts between Islamic law, the Civil Code (KUHPer), and customary (adat) law present significant challenges in integrating bilateral inheritance principles into Indonesia’s national legal framework. The existing pluralistic inheritance system often falls short in realizing social justice, particularly for women and marginalized groups, resulting in legal uncertainty and inequality. This research employs comparative legal analysis and a normative-juridical approach to explore the systematic construction of a bilateral inheritance system that guarantees equal inheritance rights for male and female heirs. The research contributes a novel hybrid legal framework that seeks to harmonize bilateral adat principles—such as equal division among children—with Islamic inheritance laws, which allocate fixed shares to specific heirs, thereby advancing both legal coherence and social equity.